Pseudouridine-Modified Phosphorodiamidate Morpholino Oligonucleotides: Synthesis and Biophysical Insights - Pratihar, Subhamoy; Kuilya, Debajyoti; Qasim, Md; Das, Arnab; Sinha, Surajit (Synlett, 2025)
The synthesis of morpholino pseudouridine chlorophosphoramidate monomer from pseudouridine and its incorporation in a 12-mer phosphorodiamidate morpholino oligonucleotide (PMO) has been successfully achieved. Thermal melting (Tm) of this PMO was performed with the complementary strand of DNA and RNA. In the case of RNA, the Tm of the base pairing between pseudouridine with A and G was comparable. Circular dichroism analysis reveals the B-type helical conformation of PMO–RNA duplexes. These advancements are expected to broaden the potential applications of PMOs in biomedical research.
Keywords: Morpholino pseudouridine; Oligonucleotides; Thermal denaturation analysis; Circular dichroism; Antisense agents